GUIDELINES FOR AUTOMOTIVE COMPONENT REPAIR USING ADDITIVE MANUFACTURING IN INDUSTRY 4.0: DESIGN AND PROCESS PERSPECTIVE - Suresh Vijaya Kumaran1; Dzuraidah Abd Wahab; Nurhasyimah Abd Aziz; Zaliha Wahid, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The advancement of Industry 4.0 technology requires industries to continuously compete in applying these technologies practically within existing processes. The remanufacturing process as one of the recovery approaches under Circular Economy strategy, is currently thriving on improvement by leveraging Industry 4.0 technology. The application of automated repair through additive manufacturing (AM) is one such opportunity to enhance remanufacturing capabilities with a variety of design options and alternative repair methods. However, AM’s potential as a repair option will be hindered due to challenges in terms of the geometric complexities, process requirements, material compatibilities and process accuracy. Hence, this study focuses on the development of guideline for repair of automotive component through AM process. The development of guideline is crucial to provide newly information and steps involved when conducting the repair using AM technology. The study is mainly focusing on remanufacturable of piston part in a crankshaft component as the case exemplary and Powder Based Fusion (PBF) of metal AM technology is used for verification purposes through experimental works. In overall, this study provides a design guideline involving repair process by using the AM process. The guideline would be useful for the designers, industries and remanufacturers to enhance the implementation of repair and remanufacturing process by adopting AM technology.